SELECTION OF OPTIMAL FORMS AND METHODS OF SCIENTIFIC AND METHODOLOGICAL WORK ON THE BASIS OF QUALIMETRIC APPROACH - Pavchenko, V.I. (Pedagogy of Higher and Secondary Education, 2009)
The article reveals essence an qualimetric approach and particularities of its use in education. Using this approach, author has developed qualimetric pattern of the selecting the optimum forms and methods of scientifically methodical work in rural school.